Être enfant à Sfax (Tunisie) - Fanny Vuaillat; Noa Schumacher; Sami Ben Fguira (L’Année du Maghreb)
The narrowing of children’s spaces is a shared hypothesis among academic circles, with deep outcomes on daily urban experiences. Cities can be restrictive and exclusive. But the city can also be a place where children can explore, discover, get to grips with spaces and the adult world, develop and experiment with social relationships. Social conditions and urban form are two potential factors in the variability of children’s everyday urban experiences.In the first part of this article, we will report on the academic discussions and how international research deals with social conditions on the one hand and urban forms on the other, without usually considering them together. The state of the literature points to the almost absence of contemporary research about the realities of children in Tunisian cities in particular, and in the Maghreb in general.Based on two periods of empirical survey in Sfax (2018 and 2019), we propose an analysis based on the hypothesis of the process of confinement of children in two heterogeneous spaces, the peri-urban aera and the Medina. For a long time, researchers described Sfax as a homogenous city with few socio-spatial contrasts and little or no residential segregation. However, rapid urban growth and selective land speculation are producing differences between neighbourhoods. The most striking disparities are between, on the one hand, villas and car-owning peri-urban area, with an over-representation of upper-class categories, and, on the other hand, the coastal area, with its concentration of working-class categories, or even those who are very poor, as in the Medina, an enclosed, dense and pedestrian aera.Within these two specific urban areas, four schools, both private and public, were involved in the surveys, with 178 pupils (10 to 12). By a mosaic approach, there are many ways of collecting data. Playing, drawing, chatting, filling in forms or weekly reports, handing disposable cameras to the children or taking them on a group walk with commentary can all be used to encourage children to express themselves in different ways.The analysis of this qualitative data is structured in two parts. First, we describe the children’s constrained spaces, and then we describe the heterogeneity of everyday urban experiences between the two groups. Children’s urban experiences, whether in the peri-urban aera or in the Medina, are characterised first and foremost by spatial constraints. Everyday spaces are limited and clearly circumscribed. On a daily basis, children from the middle and upper classes in the peri-urban aera use a small number of enclosed spaces, usually dedicated to a specific activity and always under the authority of adults. These children live a kind of extra-territoriality, so unfamiliar are they with the immediate environment of enclosed spaces. They fear and know little about the city. On the contrary, despite the dangers and fears, the children of the Medina experience their living space more intensely. The neighbourhood is physically enclosed, but children have the time and the right to negotiate their daily space. The constraints of the Medina offer possibilities. The children deal with little spaces through play. They are surrounded by adults with whom they develop a variety of relationships. Avoidance, cordiality, conflict and jokes are all ways of living together in the shared and enclosed space of the Medina.In short, children from the middle and upper classes experience a narrow urban world, while those from the Medina experience an urban world that can be explored. The difference in educational provision between state and public schools, the types of socio-educational support, family concerns and the urban conditions of each neighbourhood affect children’s lives. This research highlights the conditions that make urban spaces possible for children: neighbourhoods with identifiable boundaries and prominent landmarks; the absence of car traffic and a level of parental demands that allow time and right to “be outdoors”. The children’s everyday urban experiences provide an opportunity to document socio-spatial disparities and contribute to new knowledge about the city of Sfax.